Student Moods Before and After Body Expression and Dance Assessments. Gender Perspective - Mateu, Mercè; Garcías, Silvia; Spadafora, Luciana; Andrés, Ana; Febrer, Eulàlia (Frontiers in Psychology, 2021)
Body expression and dance are activities that contribute to the integral well-being of people. In an educational context, the process of evaluating our students implies variations in their moods. This study tackles the states of mind that students perceive before and after the evaluation of a practice in the subject of Body expression and dance, developed through choreographies, that were, previously rehearsed, and later presented to the rest of the class in a specific session. Our main interest was the obtention of information on the states of mind of the students prior to the evaluation of their choreographies (cooperative task), and again once they had been performed. The study design consisted of two phases: two different choreographies separated by an interval of 2 months. The students were asked about their moods before and after performing their choreographies, which were evaluated. The participants, 167 in total, 35 women (20.5%) and 132 men (79.5%), aged 18 to 22 years old, filled out a POMS (Profile of Mood States) questionnaire, before and after the evaluation of each occasion. Differences were found in the stress-anxiety, vigor-activity, fatigue-immobility scales and the total mood score (PGMS). In all of them, except for the fatigue-immobility scale, we found a decrease in scores after the performance, compared to scores before. For the Stress-Anxiety factor, lower values were observed in the post-tests in comparison to the pre-tests, and also lower values in the pre- and post-test scores regarding the second choreography. We conclude that the practical evaluation of the subject through choreography modifies the mood states of the students, favoring their well-being after its execution, which is why evaluation through practice is considered a positive element in the educational process.